North American combustion handbook : a basic reference on the art and science of industrial heating with gaseous and liquid fuels - Reed, Richard J. 1924- (North American Mfg. Co., 1986)
This Handbook provides a basic reference source on the Art and Science of Industrial Heating with gaseous and liquid fuels. First printed in 1952 it has been updated continuously to reflect advances in the technology behind combustion equipment and controls and is now in its third edition. More than 100,000 printed copies have been distributed worldwide. The purpose of the handbook is to provide users of combustion equipment with the following: A basic explanation of the theory of combustion; Outlines for combustion, heat transfer, and fluid calculations; Charts and data to simplify and speed these calculations; A discussion of combustion equipment, its application, selection and operation. Although the stated scope of the handbook is Industrial Heating with gaseous and liquid fuels, the reader will find that the book also contains considerable information applicable to commercial heating and to solid fuels.